Criminal women autobiographical accounts - Diana, Christina; Hicks, Jenny; O'Dwyer, Josie; Tchaikovsky, Chris (Feminist perspectives, 1985)
Criminal women tells the stories of four women who, in attempting to become women in their own making, became deeply involved in crime.--Cover.